2011
DOI: 10.1007/s10072-011-0772-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of neuroglobin after mechanical injury

Abstract: Neuroglobin (NGB) is a recently discovered globin, which is widely expressed in vertebrates central and peripheral nervous systems. Previous studies have shown that NGB is important in protecting neurons from hypoxic/ischemic brain injuries. However, there are no reports on the neuroprotective effects of NGB after mechanical injury. Currently, we showed that the NGB expression level in neurons increased continuously from 2 h after injury, and reached a peak at 16 h (p<0.01), after which it decreased sharply. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…A recent study showed that over-expression of Ngb in cultured neurons was neuroprotective against mechanical injury in vitro. This study also showed increased Ngb expression levels with peak time of 6 hours after TBI, and these increased levels correlated to the severity of TBI in rats [23]. Thus, we picked only the time point of 6 hours after TBI for examining changes of Ngb expression and 3NT production after TBI in present study.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…A recent study showed that over-expression of Ngb in cultured neurons was neuroprotective against mechanical injury in vitro. This study also showed increased Ngb expression levels with peak time of 6 hours after TBI, and these increased levels correlated to the severity of TBI in rats [23]. Thus, we picked only the time point of 6 hours after TBI for examining changes of Ngb expression and 3NT production after TBI in present study.…”
Section: Resultsmentioning
confidence: 94%
“…This examination by immunohistochemistry (Figure 1A) and western blot analysis (Figure 1B) was consistent with a report that showed a transient increase of brain Ngb expression with peak at 6 h after TBI in rats. That study also showed Ngb over-expression decreased mechanical injury-induced neuron death [23]. In our present study, quantification of western blot analysis showed that the basal levels of Ngb protein expression (149% of WT sham control mice) and the CCI-induced increase of Ngb protein levels at 6 h after TBI (196% of WT sham control mice) were significantly higher in Ngb-Tg mouse brains compared to WT TBI controls (147% of WT sham control mice) (Figure1C).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its ability to bind oxygen, neuroglobin also functions as an antioxidant and free radical scavenger [18]. Neuroglobin is expressed throughout the central and peripheral nervous systems of vertebrates [4, 14, 23, 28]. The primary sites of neuroglobin expression are the limbic system and cerebral cortex [14].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple neuroprotective effects operate by different mechanisms, including inhibit calcium in ux, reduce cellular uptake of iron, copper, and zinc, suppress necrosis and apoptosis, and several studies suggest that NGB may positively affect TBI outcomes [32,33]. The reported results indicated that there was a late, but signi cant, increase in NGB mRNA expression 7 days post-TBI in WT mice and the subacute increase occurred later that were known to be upregulated at 3 days post-TBI [32].The previous work in the rat and mouse also showed increased NGB expression levels with peak time of 6 hours after TBI [34].…”
Section: Introductionmentioning
confidence: 67%